High-efficient synthesis and biological activities of allosamidins - Huang, Gangliang; Peng, Daquan; Mei, Xinya; Chen, Xin; Xiao, Feng; Tang, Qilin (Journal of enzyme inhibition and medicinal chemistry, 2015)
The pseudo-trisaccharide allosamidin 1 is a potent inhibitor of all family-18 chitinases, and it is confirmed to have insecticidal and antifungal activities. But the synthesis of allosamidins is very difficult, and it is a challengeable subject. Allosamidins were synthesized in solid-liquid phase, total solid-phase and total liquid-phase, respectively. Solid-liquid phase method realizes the partial solid-phase synthesis of allosamidins. Total solid-phase method greatly simplifies the purification process. Total liquid-phase method shortens the synthetic steps of allosamidins. The insecticidal and antifungal activities of allosamidins were also reported herein.